Risk Factors Associated with Acute Pancreatitis after Percutaneous Biliary Intervention: We Do Not Know Nearly Enough. (6th January 2023) - Song, Jing; Deng, Jun; Wen, Feng
Abstract : Percutaneous transhepatic cholangiodrainage (PTCD) and percutaneous transhepatic biliary stenting (PTBS) may be used as a palliative treatment for inoperable patients with malignant biliary obstruction (MBO) to improve the prognosis and their quality of life. However, acute pancreatitis is a common and severe complication that cannot be ignored after PTCD and PTBS in patients with MBO. A few cases may develop severe pancreatitis with a higher mortality rate. In this study, we summarize the known risk factors for acute pancreatitis after percutaneous biliary interventional procedures and investigate possible risk factors to reduce its occurrence by early identifying high-risk patients and taking appropriate measures.